Monetary policy strategies of the European Central Bank and the Federal Reserve Bank of the US - Claudio Sardoni; L. Randall Wray (Levy Economics Institute of Bard College, 2005)
In the debate on monetary policy strategies on both sides of the Atlantic, it is now almost a commonplace to contrast the Fed and the ECB by pointing out the former's flexibility and capacity to adjust rigidity, and the latter's extreme caution, and obsession with low inflation. In looking at the foundations of the two banks' strategies, however, we do not find differences that can provide a simple explanation for their divergent behavior, nor for the very different economic performance in the U.S. and Euroland in recent years. Not surprisingly, both central banks share the same conviction that money is neutral in the long period, and even their short-term policies are based on similar fundamental principles. The two policy approaches really differ only in terms of implementation, timing, competence, etc., but not in terms of the underlying theoretical orientation. We then draw the conclusion that monetary policy cannot represent a significant variable in the explanation of the different economic performances of Euroland and U.S. The two economic areas' differences must be explained by considering other factors among which the most important is fiscal policy. Keywords: monetary policy ; federal reserve ; European central bank ; fiscal policy ; aggregate demand ; growth
Keywords: E12; E42; E58; E62; 330; Geldpolitik; Vergleich; USA; EU-Staaten